Médina Espace de la Méditerranée - HADDA, Lamia (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Dedicated to the medina in the Mediterranean space, this book is essentially based on detailed historical and photographic research into the characteristics of city design and its evolution, as well as some case studies from direct experience. The main objective of the present study consists of its documentary and evocative value, without forgetting the analysis of the multiple architectural spaces with monumental complexes of extraordinary cultural importance arranged according to precise hierarchies and specific uses. The research summarises the different experiences from this immense Arab-Muslim architectural heritage and its urban evolution. These aspects are expressed both by the large number of case studies (from Cordoba to Palermo, passing through Fez, Séfrou, Marrakech and Tunis) as well as by the quality of the built spaces as a whole. The several contributions show an urban framework that is still legible and significant, consisting of grids of houses with forms, structures and functions that show a concentration of spaces, places and monuments stratified over time and developed in the Mediterranean countries, producing extremely diverse situations.